An Attempt at a Motivic Comparison of Eduard Bagritsky’s “Ballad of Whittington” and the Seventh Part of Boris Volkov’s “Raised to the Scaffold” - Proskurina, E.N. (Studies in Theory of Literary Plot and Narratology, 2025)
The present study is an attempt to analyze the poem “In the West, the ray roars scarlet” (undated) by eastern emigrant writer B. Volkov in comparison with “The Ballad of Whittington” by E. Bagritzky (1923). Neither of these works has yet been subjected to special literary analysis. Pre-texts of Bagritsky’s ballad, such as the English fairy tale ‘Whittington and His Cat’ and R. Southey’s ‘Ingkap Reef’, have been identified. The connection between the ballad and these two works is shown at the level of several hints. The main one is the motif of the sounding bell, which plays a key role in Bagritsky’s work. When comparing it with Volkov’s poem, we analyze the elements of intertextual dialogue related both to the poetic thesaurus and to the level of grammar forms. Despite the lack of sufficient arguments in favor of the receptive character of Volkov’s poem, the method of intertextual analysis revealed the difference between the internal positions of the two authors expressed in the lyrical characters. The vagueness of the lyrical subject of ‘The Ballad of Whittington’ reflects the poet’s own mental metamorphosis in the early period of creativity, while Volkov’s lyrical self is characterized by the features of a warrior and a fighter, who found the fullness of being in a fight with fate.